Validation of voiding diary for stratification of bladder pain syndrome according to the presence/absence of cystoscopic abnormalities: a two‐centre prospective study. (25th June 2013) - Boudry, Genevieve; Labat, Jean‐Jacques; Riant, Thibault; Normand, Loïc Le; Manunta, Andrea; Bensalah, Karim; Rigaud, Jerome
<x xml:space="preserve">Abstract</x> Objective To assess the value of the voiding diary in the management of patients with bladder pain syndrome for predicting the presence or absence of cystoscopic abnormalities. Patients and Methods From November 2009 to March 2011, 54 consecutive patients (39 women and 15 men) with bladder pain syndrome, as defined by the European Society for the Study of Interstitial Cystitis/Bladder Pain Syndrome (ESSIC) criteria, were prospectively enrolled in this two‐centre study. All patients completed a home voiding diary on 3 consecutive days, which included analysis of voiding frequency, voided volume and severity of pre‐ and post‐voiding pain. The variables were evaluated on a numeric pain scale (NPS). All patients then underwent standardized cystoscopy under anaesthesia. Patients were stratified into two groups: a group with or a group without cystoscopic abnormalities. Voiding diary variables were compared using Student's t‐test. Results Cystoscopic abnormalities were found in 33 patients. The group of patients with cystoscopic abnormalities had significantly more severe frequency (P = 0.034), especially nocturnal frequency (P = 0.009), a significantly lower mean voiding volume and lower sd from the mean (P = 0.011 and P = 0.014), and a significantly lower mean post‐voiding NPS score (P = 0.039). Conclusion On analysis of the voiding diaries, we found that different patient profiles were associated with the cystoscopic appearance of the bladder. A clinical voiding score was proposed to predict the cystoscopic appearance of the bladder on the basis of the voiding diary in bladder pain syndrome but needs to be validated on an independent population.